The Association of Redox Regulatory Drug Target Genes with Psychiatric Disorders: A Mendelian Randomization Study - Zhe Lu; Yang Yang; Guorui Zhao; Yuyanan Zhang; Yaoyao Sun; Yundan Liao; Zhewei Kang; Xiaoyang Feng; Junyuan Sun; Weihua Yue (MDPI AG, 2024)
Redox regulatory drug (RRD) targets may be considered potential novel drug targets of psychosis due to the fact that the brain is highly susceptible to oxidative stress imbalance. The aim of the present study is to identify potential associations between RRD targets' perturbation and the risk of psychoses; to achieve this, Mendelian randomization analyses were conducted. The expression quantitative trait loci (eQTL) and protein QTL data were used to derive the genetic instrumental variables. We obtained the latest summary data of genome-wide association studies on seven psychoses as outcomes, including schizophrenia (SCZ), bipolar disorder (BD), major depressive disorder (MDD), attention-deficit/hyperactivity disorder, autism, obsessive-compulsive disorder and anorexia nervosa. In total, 95 unique targets were included in the eQTL panel, and 48 targets in the pQTL one. Genetic variations in the vitamin C target (OGFOD2, OR = 0.784, p = 2.14 × 10−7) and melatonin target (RORB, OR = 1.263, p = 8.80 × 10−9) were significantly related to the risk of SCZ. Genetic variation in the vitamin E (PRKCB, OR = 0.248, p = 1.24 × 10−5) target was related to an increased risk of BD. Genetic variation in the vitamin C target (P4HTM: cerebellum, OR = 1.071, p = 4.64 × 10−7; cerebellar hemisphere, OR = 1.092, p = 1.98 × 10−6) was related to an increased risk of MDD. Cognitive function mediated the effects on causal associations. In conclusion, this study provides supportive evidence for a causal association between RRD targets and risk of SCZ, BD or MDD, which were partially mediated by cognition.